Revisiting 25 years of Healthcare Studies in the SVR History - Silva, Leonardo Souza; Correa, Cleber Gimenez; Bergamasco, Leila Cristina Carneiro; Sanches, Silvio Ricardo Rodrigues (Anais do Simpósio de Realidade Virtual e Aumentada (SVR), 2023)
Healthcare is a relevant field for applications of Extended Reality (XR) technologies, allowing to aid professionals and students in the procedures training, improving the concepts and skills learning process. Over a quarter of a century, the Symposium on Virtual and Augmented Reality became one of the main channels in Brazil to discuss XR research and applications in the healthcare area. The current paper revisits past editions of the SVR, addressing studies in the healthcare area published over the years and offering an updated area overview, including categories (application, simulation, tool development, and technique). The results highlight the Rehabilitation area as one of the main fields of study; however, we might find studies in the most different medical areas. New technologies (hardware and software) create trends, such as haptic devices (Geomagic Touch), visualization devices (Oculus Rift), and game engines (Unity3D), and cost-benefit are considered. The games were employed in various studies. Statistical tests and machine learning could be further explored in the validation experiments of the applications and simulations to analyze the data.